Enhancing Early Childhood Educators' Competence: The Impact of a Structured Book Planner on Implementing the Merdeka Curriculum - Leni Kristiyanti; Enceng Mulyana; Sri Nurhayati; Lotfi Fatima Zahra (IJECA (International Journal of Education and Curriculum Application), 2025)
This study explores the effectiveness of a structured Book Planner in enhancing early childhood educators' teaching practices and aligning them with the Merdeka Curriculum’s goals. Using a pre-experimental one-group pre-test and post-test design, 45 early childhood educators from Indonesia participated in a three-month intervention. The Book Planner was integrated into their daily teaching routines to support lesson planning, thematic integration, and the practical application of curriculum principles. Data were collected using a 30-item questionnaire, field observations, and interviews. The questionnaire measured variables such as lesson planning effectiveness, curriculum alignment, and teaching confidence, and was analyzed using descriptive statistics and paired sample t-tests to assess changes before and after the intervention. Results revealed significant improvements in curriculum comprehension (from 3.87 to 4.20), lesson planning (from 3.33 to 4.28), thematic integration (from 3.71 to 4.08), and practical application (from 3.78 to 4.15). These findings highlight the Book Planner’s practical impact in enhancing educators' competencies and standardizing teaching practices, thus supporting the Merdeka Curriculum implementation. The study underscores the planner's potential to foster consistency in early childhood education, offering valuable insights for future curriculum reforms.